2015
DOI: 10.6061/clinics/2015(10)05
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin-22 genetic polymorphisms and bladder cancer risk

Abstract: OBJECTIVE:The cytokine interleukin-22 (IL-22), which is produced by T cells and natural killer cells, is associated with tumorigenesis and tumor progression in cancers. However, the role of IL-22 in bladder cancer has not been investigated.MATERIALS AND METHODS:A prospective hospital-based case-control study comprising 210 patients with pathologically proven bladder cancer and 210 age- and gender-matched healthy controls was conducted. The genotypes of 3 common polymorphisms (-429 C/T, +1046 T/A and +1995 A/C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
11
1
1
Order By: Relevance
“…Finally, a total four polymorphisms in seven studies were included . Among the seven articles, three articles investigated the gastric cancer, one investigated bladder cancer, two investigated colon cancer, and one investigated the thyroid cancer . Table shows the characteristics of included studies and Table shows the genotype distribution of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a total four polymorphisms in seven studies were included . Among the seven articles, three articles investigated the gastric cancer, one investigated bladder cancer, two investigated colon cancer, and one investigated the thyroid cancer . Table shows the characteristics of included studies and Table shows the genotype distribution of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, more and more studies suggest that IL‐22 may contribute to the pathogenesis of cancer . There were many studies that focused on the relationship between IL‐22 polymorphisms and cancer risk, but the results are still controversial. Therefore, we performed a meta‐analysis to further determine an accurate relationship between IL‐22 polymorphisms polymorphism and cancer susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found an association of a SNP in the human IL22 locus with a two‐fold risk increase for bladder cancer. Interestingly and of clinical relevance, superficial bladder cancers, which are associated with a better prognosis, were not correlated with this SNP .…”
Section: Il‐22 and Cancermentioning
confidence: 89%
“…For this review, 373 full-text articles were evaluated in depth, resulting in a final set of 112 articles for further summary (Figure 1). In total, 316 associations were extracted across all investigated outcomes as follows: age (N = 12 11-22 ), stage (N = 79 11,13,18,20,23-66 ), tumor size (N = 2 67,68 ), grade (N = 49 11,18,27,29,32,33,35…”
Section: Resultsmentioning
confidence: 99%